1956
DOI: 10.1139/b56-016
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Etiology of a Root Rot of Winter Wheat in Southwestern Ontario

Abstract: The fungus Rhizoctonia solani Kühn and the root-lesion nematode Pratylenchus minyus Sher & Allen were closely and consistently associated in naturally occurring infections of winter wheat. The resultant root rot was characterized by markedly yellowed and stunted patches of plants in the wheat fields during spring growth. In greenhouse and field experiments the combined effects of the fungus and the nematode upon growth of the wheat was almost twice as great as the effect produced when either pathogen was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…There are reports from parts of Europe (Andersen 1975) and North America (Benedict and Mountain 1956) that claim interaction between parasitic soil and root nematodes and fungal disease organisms on cereals; while Kimpinski et al 1989 claimed not to have found any significant correlations or regression relationships between population levels of root lesion nematodes in roots or soil and foliar disease severity in barley in plot experiments on Prince Edward Island. Furthermore, controlled reductions in soil nematode severity on barley in those experiments had no effect on the foliar disease severity of the crop.…”
Section: Resultsmentioning
confidence: 99%
“…There are reports from parts of Europe (Andersen 1975) and North America (Benedict and Mountain 1956) that claim interaction between parasitic soil and root nematodes and fungal disease organisms on cereals; while Kimpinski et al 1989 claimed not to have found any significant correlations or regression relationships between population levels of root lesion nematodes in roots or soil and foliar disease severity in barley in plot experiments on Prince Edward Island. Furthermore, controlled reductions in soil nematode severity on barley in those experiments had no effect on the foliar disease severity of the crop.…”
Section: Resultsmentioning
confidence: 99%
“…Ortamda Pratylenchus spp. bulunduğunda bazı bakteri ve fungusların bitkilerin kök bölgesini tahrip ettikleri; aynı bakteri ve fungusların Pratylenchus türlerinin ortamda bulunmadığı durumlarda ise yaptıkları zararın önemsiz olduğu bildirilmektedir (Benedict & Mountain, 1956). …”
Section: Araştırma Sonuçları Ve Tartışmaunclassified
“…Nematode lesions can be enlarged by fungi and bacteria that invade and multiply in the wounds (Powell 1971;Taheri et al 1994). In Canada, wheat root rot was significantly more severe when P. neglectus occurred together with the fungus Rhizoctonia solani kühn (Benedict and Mountain 1956). Physiological changes occurring in plants infected with nematodes can enhance their susceptibility to attacks by fungi, whether pathogenic or nonpathogenic (Powell 1971).…”
Section: [Effet Du Nématode Des Lésions De Racines (Pratylenchus Penementioning
confidence: 99%